Supporting and Constraining Factors in the Implementation of Narcotics Rehabilitation Programs at the Class IIA Muaro Padang Correctional Institution - Chania, Lutfiah; Alhadi, Zikri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine various factors influencing the implementation of the Narcotics Rehabilitation Program for Correctional Inmates at the Class IIA Muaro Padang Correctional Institution, including both supporting and inhibiting factors. Rehabilitation programs for narcotics abusers constitute an essential component of the correctional system, as they focus on recovery processes, guidance, and the enhancement of inmates’ social capacities to enable them to function productively after completing their sentences. This study employs a qualitative approach using a descriptive method. Data were collected through in-depth interviews with correctional officers and program administrators, direct observation of rehabilitation activities, and document analysis related to program implementation and policy. The findings indicate that program effectiveness is supported by the commitment and active involvement of correctional officers, the existence of internal regulations that promote rehabilitation activities, and coordination with relevant institutions in the implementation of inmate guidance. However, the study also identifies several obstacles, including the limited number of human resources with specialized competencies in narcotics rehabilitation, inadequate facilities and infrastructure, insufficient budgetary support, and limited quotas for inmate participation in the program. In addition, variations in inmates’ levels of motivation and awareness further complicate the implementation of rehabilitation activities. Based on these findings, this study emphasizes that the success of narcotics rehabilitation programs is strongly influenced by resource readiness, inter-institutional collaboration, and institutional capacity building to ensure that rehabilitation objectives can be achieved optimally and sustainably.